Navodila za inventuro sestojev in ureditev obrata na posestvu Snežnik od leta 1906 naprej - Perko, Franc (Gozdarski vestnik, 2006)
In the article are presented the Instructions which Heinrich Schollmayer prepared in 1906 for the management of plenter forests on the Snežnik estate. The instructions prescribed accurate determination of growing stock (measurement of all trees) and of increment (drilling with increment borers), as well as precise monitoring of forest management. Schollmayer determined an optimal plenter structure of the stands and set it as his management goal. In accordance with the instructions and drawn plans he developed the so-called control method of forest management.
Keywords: forestry; gozdarstvo; lesne zaloge; sestoji; prirastek; dendrometrija; prebiralni gozd; Snežnik; navodila; zgodovinski pregledi